Next Generation Sequencing of Circulating Cell-Free DNA for Evaluating Mutations and Gene Amplification in Metastatic Breast Cancer. (6th January 2020) - Page, Karen; Guttery, David S; Fernandez-Garcia, Daniel; Hills, Allison; Hastings, Robert K; Luo, Jinli; Goddard, Kate; Shahin, Vedia; Woodley-Barker, Laura; Rosales, Brenda M; Coombes, R Charles; Stebbing, Justin; et al.
Abstract: BACKGROUND: Breast cancer tissues are heterogeneous and show diverse somatic mutations and somatic copy number alterations (CNAs). We used a novel targeted next generation sequencing (NGS) panel to examine cell-free DNA (cfDNA) to detect somatic mutations and gene amplification in women with metastatic breast cancer (MBC). METHODS: cfDNA from pretreated patients (n = 42) and 9 healthy controls were compared with matched lymphocyte DNA by NGS, using a custom 158 amplicon panel covering hot-spot mutations and CNAs in 16 genes, with further validation of results by droplet digital PCR. RESULTS: No mutations were identified in cfDNA of healthy controls, whereas exactly half the patients with metastatic breast cancer had at least one mutation or amplification in cfDNA (mean 2, range 1–6) across a total of 13 genes. Longitudinal follow up showed dynamic changes to mutations and gene amplification in cfDNA indicating clonal and subclonal response to treatment that was more dynamic than cancer antigen 15-3 (CA15-3). Interestingly, at the time of blood sampling disease progression was occurring in 7 patients with erb-b2 receptor tyrosine kinase 2 ( ERBB2 ) gene amplification in their cfDNA and 3 of these patients were human epidermal growth factor receptor 2 (HER2) negative at diagnosis, suggesting clonal evolution to a more aggressive phenotype. Lastly, 6 patients harbored estrogen receptor 1 ( ESR1 ) mutations in cfDNA, suggesting resistance to endocrine therapy. Overall 9 of 42 patients (21%) had alterations in cfDNA that could herald a change in treatment. CONCLUSIONS: Targeted NGS of cfDNA has potential for monitoring response to targeted therapies through both mutations and gene amplification, for analysis of dynamic tumor heterogeneity and stratification to targeted therapy.